2022
DOI: 10.7753/ijsea1112.1031
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Energy Loss in a Stepped Spillway Equipped with Inclined Steps in the Nappe and Skimming Flow Regimes

Abstract: Scrutinizing the considerable flow energy in a spillway plays a significant role in maintaining downstream dam safety, and due to this fact, the dimension of the stilling basin will be enormously reduced, and from an economical point-of-view, construction costs will dramatically reduce. This phenomenon may even result in the removal of the stilling basin. A stepped spillway is one of the best structures for this purpose. In this experimental study, steps in the stepped spillway are equipped with inclined steps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Kamyab Moghaddam et al also conducted an experimental static pressure analysis in stepped chutes with inclined steps. The results show inclined steps increasing the static pressure on the steps [11].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Kamyab Moghaddam et al also conducted an experimental static pressure analysis in stepped chutes with inclined steps. The results show inclined steps increasing the static pressure on the steps [11].…”
Section: Introductionmentioning
confidence: 90%
“…Hamedi et al has conducted experiments on the stepped chute with reverse inclined steps to observe the efficiency of energy dissipation for the stepped spillway [3]. Kamyab Moghaddam et al completed a series of experiments to determine the energy loss in different step modifications in the same physical model used in this research [4][5]. The results show a slight increase in the energy loss rate when a reverse inclined step is applied.…”
Section: Introductionmentioning
confidence: 99%
“…Elaborating on their methodology, a similar approach was applied in the recent study to assess flow characteristics. The experimental results were subsequently compared with those obtained by Kamyab Moghaddam et al, with the aim of evaluating the model's accuracy (12). To simulate the Ogee spillway, the required geometry and parameters were similar to the aforementioned spillway, with the removal of steps while maintaining the slope of the spillway body.…”
Section: Methodsmentioning
confidence: 99%
“…Their results demonstrated that the static pressure in the middle of the step is higher than the static pressure on the right and left sides of the steps at all discharge rates. Inspired by their work, a similar approach and location for the piezometers has been adopted in this research to study and examine pressure fluctuations in the stilling basin, the results compared to their work to confirm the accuracy of the model (22). Zienkiewicz and Moriguchi et al showed different parts of the basin experience varying levels of pressure, with the maximum values typically occurring in the initial parts of the basin due to the direct impact of the water jet on the first blocks.…”
Section: Pressure In Hydraulic Structuresmentioning
confidence: 96%